Suboptimal glycemic control among subjects with diabetes mellitus in India: a subset analysis of cross-sectional wave-7 (2016) data from the International Diabetes Management Practices Study (IDMPS). (June 2020) - Ramachandran, Ambady; Jain, Sunil M.; Mukherjee, Sagarika; Phatak, Sanjeev; Pitale, Shailesh; Singh, Shailendra K.; Agrawal, Navneet; Majumdar, Anirban; Deshpande, Neeta; Jhulka, Sandeep; Minakshisundaram, Shunmugavelu; Chawla, Manoj; et al.
Objective: To assess the real-world management practices of subjects with type 2 diabetes mellitus (T2DM) and type 1 diabetes mellitus (T1DM) in India. Methods: This cross-sectional study was conducted between 7 March 2016 and 15 May 2016 in India as part of the seventh wave (2016) of the International Diabetes Management Practices Study (IDMPS). Adult subjects with T1DM or T2DM visiting physicians during a 2-week recruitment period were included. Results: A total of 55 physicians included 539 subjects who met eligibility criteria. Of 495 subjects with T2DM, 303 were treated with oral glucose lowering drugs (OGLDs) only, 158 were treated with OGLD + insulin, and 27 received insulin only. Among 44 subjects with T1DM receiving insulin, 13 (29.5%) were also treated with OGLD therapy. The most commonly used insulin regimens were basal alone (69/184; 37.5%) and premixed alone (63/184; 34.2%) in subjects with T2DM, and basal + prandial insulin (24/44; 54.5%) in subjects with T1DM. Proportions of subjects achieving glycemic targets were low [glycated haemoglobin (HbA1c) <7%: T1DM = 7.3% (3/44), T2DM = 25.2% (106/495); as targeted by the treating physician: T1DM = 31.8% (14/44), T2DM = 32.1% (59/185); global target: T1DM = 4.8% (2/42) and T2DM = 1.7% (8/482)]. In subjects with T2DM, HbA1c <7% was noted in 11/22 subjects receiving insulin only and 76/260 receiving only OGLDs. Lack of experience in self-managing insulin dosing, poor diabetes education and failure to titrate insulin dosages were the main reasons for non-achievement of glycemic targets. Conclusion: Timely insulinization, education and empowerment of people with diabetes may help improve glycemic control in India.